APPLICATION OF HALAL VALUE CHAIN MANAGEMENT PRINCIPLES IN BAKERY AND CAKE AT PADANGSIDIMPUAN CITY - Ade Khadijatul. Z Hrp; Andri Soemitra; Zuhrinal M. Nawawi; Rahmat Rahmat (Institut Agama Islam Negeri Padngsidimpuan, 2023)
AbstractNot only does Halal certification provide superior legal protection for Muslim consumers' rights to non-halal products, but it also increases the selling value of business actors' products because consumers are more willing to buy goods from them. Inconsistencies in the halal value chain will result from the use of different local halal value chain standards, particularly logistics that are not aligned with international halal logistics standards. The purpose of this study is to explain the application of halal value chain management to processed bakery and chake products in Padangsidimpuan City using an empirical descriptive approach. The following processes are included in the implementation of halal value chain management for halal-certified bakery and chake products in Padangsidimpuan City: a. purchasing, b. acceptance, c. production, d. warehousing, e. distribution, and f. the product is not used up. That the majority of bakery and chake businesses have implemented halal value chain management in their operations. Furthermore, all stakeholders in the halal certification process receive valuable input.